2018
DOI: 10.4103/0366-6999.238138
|View full text |Cite
|
Sign up to set email alerts
|

Gender Affects the Median Effective Dose and 95% Effective Dose of Oxycodone for Blunting the Hemodynamic Response to Tracheal Intubation in Narcotic-Naïve Adult Patients

Abstract: Background:Intravenous (IV) oxycodone has been used at induction to prevent an intubation reaction. The aims of the current study were to calculate the median effective dose (ED50) and the 95% effective dose (ED95) of an IV bolus of oxycodone that blunts the hemodynamic response to tracheal intubation with propofol according to gender and to observe the adverse events of induction-dose oxycodone.Methods:Adult patients who required general anesthesia and tracheal intubation were enrolled. Tracheal intubation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…In contrast, human males have been found to require 30%‐40% more morphine to obtain similar analgesic effects compared to females . Similarly, a recent patient study also found that men required 28% more oxycodone than females to blunt the intubation reaction . Our model found that oxycodone is more potent in males compared to females.…”
Section: Discussionmentioning
confidence: 42%
See 3 more Smart Citations
“…In contrast, human males have been found to require 30%‐40% more morphine to obtain similar analgesic effects compared to females . Similarly, a recent patient study also found that men required 28% more oxycodone than females to blunt the intubation reaction . Our model found that oxycodone is more potent in males compared to females.…”
Section: Discussionmentioning
confidence: 42%
“…34 Similarly, a recent patient study also found that men required 28% more oxycodone than females to blunt the intubation reaction. 37 Our model found that oxycodone is more potent in males compared to females. Our finding suggests that the dose-effect difference between males and females is not due to pharmacokinetics, as no gender differences were found in the PK model.…”
Section: Cns Effectsmentioning
confidence: 77%
See 2 more Smart Citations
“…The progress of OAA/S assessment was performed by a well‐trained, blinded researcher . Respiratory depression was defined as respiratory rate decreased to <10 beats/min …”
Section: Methodsmentioning
confidence: 99%